First record of Seuratum sp. (Nematoda: Seuratidae) in Chrotopterus auritus (Chiroptera: Phyllostomidae) from Mexico - Panti-May, Jesús Alonso; MacSwiney G., María Cristina; Ortega, Jorge; Moguel-Chin, Wilson Isaias (Therya Notes, 2025)
Chrotopterus auritus is a rare carnivorous species in the Neotropical region. The helminth fauna of this bat is poorly known, with only 1 published record in Peru. In Mexico, C. auritus is classified as endangered, mainly due to deforestation. The study of helminths in wildlife is relevant, as they can influence behavior, population dynamics, and evolution of their hosts, regulating populations and contributing to the maintenance of biodiversity. As a part of a DNA barcoding survey of bats in Mexico, a specimen of C. auritus was examined for helminths. Only three adult female nematodes were recovered from the intestine of this bat. Nematodes were morphologically studied using light microscopy and scanning electron microscopy. In addition, the 28S ribosomal RNA (28S) gene and the cytochrome c oxidase subunit 1 (COI) gene of 1 specimen were amplified and sequenced. Nucleotide sequences obtained from our specimen were used for phylogenetic analyses. The morphology observed in 2 specimens (e. g. cephalic structures, esophagus, rows of spines, vulva, and tail) agreed with characteristics established for the genus Seuratum. Phylogenetic analyses of the superfamily Seuratoidea grouped our 28S and COI sequences of Seuratum sp. with Paraquimperia sp., a species of the family Quimperiidae. The morphology observed in the female specimens differ from those reported for Seuratum cancellatum, the only species reported from Neotropical bats. This suggests that the specimens found in Yucatan represent a distinct, potentially new species. However, additional specimens, particularly males, are needed to confirm this hypothesis. This study provides the first helminthological record in C. auritus from Mexico, as well as the first 28S and COI sequences for members of the family Seuratidea.